Penguatan Kompetensi Asesmen Pembelajaran Bagi Guru Melalui Pelatihan Berbasis Praktik Kolaboratif - Muryati Muryati; Muhlis Fajar Wicaksana; Sukarno Sukarno; Sri Wahono Saptomo (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2025)
Strengthening teachers' competence in learning assessment is a crucial aspect of improving education quality, particularly for teachers as the implementers of learning in educational institutions. This community service activity aimed to enhance teachers' skills in designing, implementing, and evaluating learning assessments through collaborative, practice-based training. The activity was conducted in March 2025 in Surakarta, involving 30 junior high school teachers from Sekolah Penggerak. The implementation methods included workshops, focused group discussions (FGDs), and hands-on group practice in developing assessment instruments. Evaluation results showed that 83% of participants clearly understood the objectives of the training, 70% reported a strong understanding of formative, summative, and diagnostic assessments, and 80% stated that the hands-on practice significantly helped in designing differentiated assessments. Furthermore, 80% of participants felt a notable improvement in their competence, particularly in managing student diversity through appropriate assessment methods. Collaborative, practice-based training proved effective in fostering active participation, joint problem-solving, and the development of teacher learning communities. The activity recommends ensuring the sustainability of training programs with ongoing mentoring to strengthen the implementation of quality assessments in classrooms.